2007
DOI: 10.2174/157339707779815722
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Controversies in Autoantibodies Associated with Systemic Rheumatic Diseases

Abstract: Since the first identification of self-reactive antibodies in systemic lupus erythematosus and other systemic autoimmune rheumatic diseases, many autoantibodies have been identified as useful probes in molecular and cell biology and as diagnostic and prognostic biomarkers in clinical immunology. Among the autoantigens, double-stranded desoxoribonucleic acid (dsDNA), the Smith antigen (Sm), ribonucleoproteins (RNP), Scl-70 (topoisomerase I), proliferating cell nuclear antigen (PCNA), and others were described a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 159 publications
(206 reference statements)
0
19
0
Order By: Relevance
“…Standardization of autoantibody tests and method of choice for the detection of anti-Rib-P antibodies Today, a variety of assay platforms are available for the detection of anti-Rib-P antibodies including LIA, ELISA and ALBIA [6,9,19,21,36,37]. The antigens used in those tests range from short synthetic peptides and recombinant proteins to affinity-purified macromolecular complexes.…”
Section: Association With Age and Clinical Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…Standardization of autoantibody tests and method of choice for the detection of anti-Rib-P antibodies Today, a variety of assay platforms are available for the detection of anti-Rib-P antibodies including LIA, ELISA and ALBIA [6,9,19,21,36,37]. The antigens used in those tests range from short synthetic peptides and recombinant proteins to affinity-purified macromolecular complexes.…”
Section: Association With Age and Clinical Parametersmentioning
confidence: 99%
“…Furthermore, clinical correlations with lupus nephritis [7] or hepatitis [8] have been described, although these findings have not been uniformly observed in all studies and thus are still debated [9]. Evidence for a pathogenic role of anti-Rib-P aabs continues to mount.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have demonstrated that CSF samples from patients with active RRMS (aRRMS) are enriched in memory BC and that persisting plasma blasts (PB) are a major source of antibody secreting cells (ASC) during and beyond phases of disease activity there is limited knowledge as to the distribution of distinct BC-subtypes among peripheral and CSF immune cells and how they relate to disease activity or change composition during immunomodulatory treatment [4,5]. Furthermore, it is unknown whether MS is associated with changes in peripheral BC-homeostasis as described for several collagen vascular disorders which share the production of auto-antibodies as a common immune abnormality [9]. In healthy adults the peripheral BC-compartment comprises 60e70% IgD þ CD27 À naïve and 30e40% memory BC, which further divide into IgD À CD27 þ class-switched (CSM-BC), IgD þ CD27 þ unswitched (USM-BC), and a minor portion of IgD À CD27 À doublenegative (DNM-BC) memory BC [10].…”
Section: Introductionmentioning
confidence: 99%